RURAL SOCIO ENTREPRENEUR THROUGH VILLAGE-OWNED ENTERPRISES (BUMDes) IN TEGALWARU BOGOR - I Made Indra P.; Fanny Novika; Wahyuari Wahyuari; Robidi Robidi; Nike Septivani (Yayasan Education and Social Center, 2022)
Village economic progress can create because of the contribution of a strong rural economy. At the same time, there are certain advantages to living in rural areas (rural). Some drawbacks include the absence of facilities and infrastructure necessary to support the input process and post-rural production, making it difficult for rural businesses to compete on a level playing field. Therefore, an effort is needed to overcome economic problems, especially by developing the concept of socio-entrepreneur in rural communities (rural). This study used qualitative research methods, and the research carries out in Tegalwaru Village, Bogor. Data collection used several techniques, namely in-depth interviews, non-participant observations, and documentation studies. The results of the research Tegal Waru Village is one example village that has developed the concept of a rural entrepreneur well with the help of the Foundation. The role of Bumdes already exists, but it is not yet effective. Bumdesa can do licensing and marketing assistance to invite wider parties. Some activities need to be developed through Edu Ecotourism and oil palm tourism